Use of chemical indicators of beer aging for ex-post checking of storage conditions and prediction of the sensory stability of beer - Cejka, Pavel; Culík, Jiří; Horák, Tomáš; Jurková, Marie; Olšovská, Jana (Journal of agricultural and food chemistry, 2013)
The rate of beer aging is affected by storage conditions including largely time and temperature. Although bottled beer is commonly stored for up to 1 year, sensorial damage of it is quite frequent. Therefore, a method for retrospective determination of temperature of stored beer was developed. The method is based on the determination of selected carbonyl compounds called as "aging indicators", which are formed during beer aging. The aging indicators were determined using GC-MS after precolumn derivatization with O-(2,3,4,5,6-pentaflourobenzyl)hydroxylamine hydrochloride, and their profile was correlated with the development of old flavor evolving under defined conditions (temperature, time) using both a mathematical and statistical apparatus. Three approaches, including calculation from regression graph, multiple linear regression, and neural networks, were employed. The ultimate uncertainty of the method ranged from 3.0 to 11.0 °C depending on the approach used. Furthermore, the assay was extended to include prediction of beer tendency to sensory aging from freshly bottled beer.
Keywords: Taste; Gas Chromatography-Mass Spectrometry; Time Factors; časové faktory; Temperature; skladování potravin; lidé; pivo; Beer; Flavoring Agents; Food Storage; plynová chromatografie s hmotnostně spektrometrickou detekcí; teplota; chuť; chuťové esence; Humans